Design, Synthesis, and Biological Evaluation of a New Series of Biphenyl/Bibenzyl Derivatives Functioning as Dual Inhibitors of Acetylcholinesterase and Butyrylcholinesterase - Dong-mei Wang (Molecules, 2017)
Alzheimer’s disease (AD), the most common form of dementia in adults, is a progressive neurodegenerative disorder of the brain characterized by loss of memory and steady deterioration of cognition. Here, a series of symmetrical molecules containing biphenyl/bibenzyl scaffolds (12–36) were designed, synthesized, and evaluated for their ability to inhibit both acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). A biological evaluation showed that most of these biphenyl derivatives were potent AChE and BuChE inhibitors. Among them, compound 15 displayed the greatest ability to inhibit BuChE (IC50 = 0.74 µM) and was also a good AChE inhibitor (IC50 = 1.18 µM). Compound 19 was not only a potent AChE inhibitor (IC50 = 0.096 µM), but also a mild BuChE inhibitor (IC50 =1.25 µM). Overall, these results suggested that compound 19 may be a promising agent in the treatment of AD.